A test to assess aptitudes in candidates who want to enter interpreting studies at FLEX (Islas, 2022)
AbstractThis diploma paper is intended to elucidate why aptitudes are required to accomplish a high performance in interpreting and to support the idea that an aptitude test could be beneficial at FLEX in order to know which students are more likely to become successful interpreters. With the implementation of the new Plan E, which is intended to separate the field of Translation and Interpretation from the field of Linguistics, an efficient test for the assessment of aptitudes in those students who will take the field of Translation and Interpretation could be helpful.
Keywords: Interpretation; interpretation process; aptitude test; performance